Guidance solutions for multiple vehicle assembly - Okasha, Mohamed Elsayed Aly Abd Elaziz (Trans Tech Publications, Switzerland, 2014)
This paper exploits the guidance algorithms to assembly multiple vehicle in close proximity. The objective is to move each vehicle in the assembly to its final location. The guidance laws are determined such that, each vehicle should attract to the others on long distances and avoid collision with them in short distances. These laws are based on Lyapunov’s second method that utilize the potential function theory to insure the stability of the assembly process. Numerical investigations were performed for different configurations of the assembly. The proposed algorithms may prove useful for future mission applications such as satellite formation flying, structures assembly in space and mobile robots control.